Quality of Service Comparison of LOS and NLOS Propagation in a LoRaWAN-Based Remote Monitoring System - Fikri Nizar Gustiyana; Muntaqo Alfin Amanaf; Danny Kurnianto (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
Indonesia is an agricultural country with a wealth of natural resources. The agricultural sector is one of the natural resources with great potential. The processing and monitoring of very large agricultural land is currently a problem that must be resolved as soon as possible. The use of a remote monitoring system is the solution to this problem. The LoRa protocol is one of the communication protocols that can be used on large farms. This communication system is part of the low-power wide-area network communication system. The LoRaWAN communication system was implemented on agricultural soil moisture monitoring devices in this study. Based on the findings, it is possible to conclude that the propagation used at the time of transmission influences the success rate of data transmission via LoRaWAN communication. Line of Sight (LOS) propagation has a higher success rate than Non Line of Sight (NLOS) propagation. The LOS value is 17% greater than the NLOS at a distance of 100 meters. The LOS value is 24% greater than the NLOS at a distance of 150 meters. The LOS value is 3% greater than the NLOS value at a distance of 200 meters. LOS propagation measurement throughput is higher than NLOS propagation measurement throughputKeywords: LoRa, LoRaWAN, Wireless, Internet Of Things